2016
DOI: 10.1016/j.jprot.2015.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics reveals the mechanism and consequence of gliotoxin-mediated dysregulation of the methionine cycle in Aspergillus niger

Abstract: a b s t r a c t a r t i c l e i n f oGliotoxin (GT) is a redox-active metabolite, produced by Aspergillus fumigatus, which inhibits the growth of other fungi. Here we demonstrate how Aspergillus niger responds to GT exposure. Quantitative proteomics revealed that GT dysregulated the abundance of 378 proteins including those involved in methionine metabolism and induced de novo abundance of two S-adenosylmethionine (SAM)-dependent methyltransferases. Increased abundance of enzymes S-adenosylhomocysteinase (p = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 61 publications
2
27
0
Order By: Relevance
“…This implies that GliT activity effectively compensates for the absence of GtmA in A. fumigatus Δ gtmA and that GtmA may have been an ancestral protective strategy against gliotoxin and/or other ETPs prior to the acquisition of the gliotoxin cluster by this organism. The presence of MT-II in non-ETP producing A. niger supports this hypothesis as MT-II has been shown to be involved in protection against gliotoxin and possibly other ETPs [15]. Subsequent redundancy of this superseded protection mechanism in A. fumigatus may have resulted in the neofunctionalization of GtmA and its interlinked association with the gliotoxin biosynthetic gene cluster.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This implies that GliT activity effectively compensates for the absence of GtmA in A. fumigatus Δ gtmA and that GtmA may have been an ancestral protective strategy against gliotoxin and/or other ETPs prior to the acquisition of the gliotoxin cluster by this organism. The presence of MT-II in non-ETP producing A. niger supports this hypothesis as MT-II has been shown to be involved in protection against gliotoxin and possibly other ETPs [15]. Subsequent redundancy of this superseded protection mechanism in A. fumigatus may have resulted in the neofunctionalization of GtmA and its interlinked association with the gliotoxin biosynthetic gene cluster.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, it was shown that disruption of the uncharacterized methyltransferase MT-II in A. niger resulted in increased sensitivity to exogenous gliotoxin. Like GtmA, recombinantly expressed MT-II was shown to sequentially bis -thiomethylate dithiol gliotoxin, forming monomethylgliotoxin (MmGT) and then BmGT [15]. MT-II is an orthologue of GtmA (53% sequence identity), despite the fact that this organism does not produce gliotoxin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gliotoxin exposure induces elevated GtmA abundance in A. fumigatus DgliT, 9 and Manzanares-Miralles et al reported that gliotoxin induces significantly increased abundance of the GtmA ortholog in Aspergillus niger, in which the gli cluster is absent. 37 Interestingly, while Zn 2+ exposure alone had no significant effect on the abundance of GtmA in A. fumigatus, combinatorial exposure with gliotoxin resulted in significantly elevated GtmA abundance (18.8-fold and p o 0.01) compared to that in the presence of gliotoxin only (Table 2). Allied to GtmA activity data (Fig.…”
Section: +mentioning
confidence: 94%
“…All media used were as previously described by 20. Cultures were grown at 30°C with shaking at 200 rpm.…”
Section: Methodsmentioning
confidence: 99%